General Pharmacological Properties of YJA20379-8, a New H+/K+-ATPase Inhibitor with Anti-ulcer Activities - Lee, Eun-Bang; Cho, Sung-Ig; Chang, Hae-Ok; Chang, Man-Sik; Kim, Kyu-Bong; Lee, Seok-Bong; Choi, Wahn-Soo (Arzneimittelforschung, 2001)
The general pharmacological properties of YJA20379-8(3-butyryl-4-[(R)-1-methyl-benzylamino]-8-ethoxy-1,7-naphthyrid-ine, CAS 187654-40-6), a new H+/K+-ATPase inhibitor with anti-ulcer activities, were investigated in mice, rats and guinea pigs. YJA20379-8 at oral doses of 25, 50 and 100 mg/kg did not affect the locomotor activity, hexobarbital hypnosis and motor coordination in mice. The drug did not have analgesic action and anticonvulsant action at the doses of 100 mg/kg p.o. The respiration and blood pressure were not affected at 10 mg/kg i.v. in rats. YJA20379-8 at 2 ×10−4 g/ml did neither produce any contraction nor relaxation of isolated organs, such as guinea pig ileum, rat fundus, rat uterus and guinea pig vas deferens, and the drug antagonized the contractile responses to several spasmogens, such as acetylcholine, histamine, serotonin, L-phenylephrine, oxytocin and BaCl2. The drug up to 100 mg/kg p.o. did not affect pupil size and the intestinal propulsion of mice. And it did not show an anticarrageenan action at 100 mg/kg. In this general pharmacology study, hypothermic effect in mice, retardation in gastric emptying in rats, decreases in urine excretion in rats at oral doses of 50 and 100 mg/kg of YJA20379-8 and the spasmolytic activity could be found. However, no other effects were exhibited at a high oral dose of 100 mg/kg in animals in this study.
Keywords: Anti-ulcer drug; 3-Butyryl-4-[(R)-1-methyl-benzylamino]-8-ethoxy-1,7-naphthyridine; CAS 187654-40-6; Proton pump inhibitor; YJA20379-8, general pharmacology